Dukungan Lingkungan Sosial Budaya terhadap Kemampuan Petani dalam Pengelolaan Hutan Kemiri di Kabupaten Maros Provinsi Sulawesi Selatan - Adi Riyanto Suprayitno; Sumardjo Sumardjo; Darwis S Gani; Basita Ginting Sugihen (Jurnal Penyuluhan, 2012)
living around the candlenut forest in Maros District have been managing and utilizing candlenut forest since 1826. These activities have been part of their daily living activities. The existence of candlenut forest is a successful evidence of farmers ability in managing that forest. It is presumed that the cultural social environtment has important roles to form the farmers’ ability to manage and to utilize candlenut forest. The research intended to analyze the contribution of cultural social environment to farmers’ ability in managing and utilizing candlenut forest. The data were collected on January-Maret 2010 in Maros District, South Sulawesi Province using some methods: questionnare list, interview, observation, and documents. The data were analyzed using (1) descriptive statistics, and (2) inferensial statistics based on SEM using LISREL 8.70 software programming. The result shows that farmers’ contribution of cultural social environment, today is low. It, however, has a positive contribution for increasing farmers’ ablity.Key words: Cultural social environment, farmers ability, community candlenut forest